Pengaruh Pembelajaran Berdiferensiasi terhadap Motivasi Belajar dan Kemampuan Komunikasi Matematis Siswa - Hartati, Siti (Yayasan Sembilan Pemuda Indonesia, 2025)
The observation results show that students' learning motivation and mathematical communication skills are at a low level. To overcome this, this study applies differentiated learning as a strategy to improve students' learning motivation and mathematical communication skills. The main objective of this study is to identify the effect of differentiated learning on both aspects. The method used in this study is an experiment with a Pretest-Posttest Control Group design. The results of the study stated that differentiated learning has a positive influence on the learning motivation of class VIII students at MTS Miftahul Ulum Banyuasin III. However, differentiated learning did not show a significant influence on students' mathematical communication abilities.